Monetary policy rules for managing aid surges in Africa - Adam, C; O'Connell, S; Buffie, E; Pattillo, C (Blackwell Publishing Ltd, 2009)
This paper examines the properties of alternative monetary policy rules in response to large aid surges in low-income countries characterized by incomplete capital market integration and currency substitution. Using a dynamic stochastic general equilibrium model, it is shown that simple monetary rules that stabilize the path of expected future seigniorage for a given aid flow have attractive properties relative to a range of conventional alternatives, including those involving heavy reliance on bond sterilization or a commitment to a pure exchange rate float. These simple rules, which are shown to be robust across a range of fiscal responses to aid inflows, appear to be consistent with actual responses to recent aid surges in a range of post-stabilization countries in Sub-Saharan Africa.